1999
DOI: 10.1074/jbc.274.42.29720
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Functional Interaction of the Catalytic and Regulatory Subunits of Human Methionine Adenosyltransferase in Mammalian Cells

Abstract: . The recombinant MAT II ␣ 2 and r␤ subunit associated spontaneously either in cell-free system or in COS-1 cells coexpressing both subunits. Analysis of nickel-agarosepurified His-tagged r␣ 2 subunit from COS-1 cell extracts showed that the ␤ subunit co-purified with the ␣ 2 subunit. Furthermore, the ␣ 2 and ␤ subunits co-migrated in native polyacrylamide gels. Together, the data provide evidence for ␣ 2 and ␤ MAT subunit association. In addition, the ␤ subunit regulated MAT II activity by reducing its K m fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
122
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(124 citation statements)
references
References 30 publications
(29 reference statements)
2
122
0
Order By: Relevance
“…In contrast to MAT ␣ subunits, which are highly conserved throughout evolution, the ␤ subunit of MAT II seems to be only present in the mammalian species (15,19). Recently, we cloned and characterized the human MAT II ␤ subunit (26,31), found that it has no catalytic activity, and confirmed that it acts as a regulatory subunit for the enzyme. When ␤ associates with the ␣ subunit it alters its kinetic properties and renders MAT II more susceptible to product inhibition by AdoMet (26,31).…”
Section: Methionine Adenosyltransferase (Mat)mentioning
confidence: 96%
See 4 more Smart Citations
“…In contrast to MAT ␣ subunits, which are highly conserved throughout evolution, the ␤ subunit of MAT II seems to be only present in the mammalian species (15,19). Recently, we cloned and characterized the human MAT II ␤ subunit (26,31), found that it has no catalytic activity, and confirmed that it acts as a regulatory subunit for the enzyme. When ␤ associates with the ␣ subunit it alters its kinetic properties and renders MAT II more susceptible to product inhibition by AdoMet (26,31).…”
Section: Methionine Adenosyltransferase (Mat)mentioning
confidence: 96%
“…Recently, we cloned and characterized the human MAT II ␤ subunit (26,31), found that it has no catalytic activity, and confirmed that it acts as a regulatory subunit for the enzyme. When ␤ associates with the ␣ subunit it alters its kinetic properties and renders MAT II more susceptible to product inhibition by AdoMet (26,31). Interestingly, the human ␤ subunit can also interact with the ␣1 subunit of MAT I/III and the Escherichia coli ␣ MAT subunit and alter their kinetic properties as well (26,31).…”
Section: Methionine Adenosyltransferase (Mat)mentioning
confidence: 96%
See 3 more Smart Citations